Involvement of MCH-oxytocin neural relay within the hypothalamus in murine nursing behavior - Yoko Kato; Harumi Katsumata; Ayumu Inutsuka; Akihiro Yamanaka; Tatsushi Onaka; Shiro Minami; Chitose Orikasa (Scientific Reports, 2021)
Abstract Multiple sequential actions, performed during parental behaviors, are essential elements of reproduction in mammalian species. We showed that neurons expressing melanin concentrating hormone (MCH) in the lateral hypothalamic area (LHA) are more active in rodents of both sexes when exhibiting parental nursing behavior. Genetic ablation of the LHA-MCH neurons impaired maternal nursing. The post-birth survival rate was lower in pups born to female mice with congenitally ablated MCH neurons under control of tet-off system, exhibiting reduced crouching behavior. Virgin female and male mice with ablated MCH neurons were less interested in pups and maternal care. Chemogenetic and optogenetic stimulation of LHA-MCH neurons induced parental nursing in virgin female and male mice. LHA-MCH GABAergic neurons project fibres to the paraventricular hypothalamic nucleus (PVN) neurons. Optogenetic stimulation of PVN induces nursing crouching behavior along with increasing plasma oxytocin levels. The hypothalamic MCH neural relays play important functional roles in parental nursing behavior in female and male mice.